Gender issues and sexuality essential primary sources - Lerner, K. Lee.; Lerner, Brenda Wilmoth; Lerner, Adrienne Wilmoth; Gale Group (Detroit, Michigan Gale, 2006)
A focus on leading social issues of the 19th, 20th, and 21st centuries. Each title contains approximately 175 full or excerpted documents---speeches, legislation, magazine and newspaper articles, essays, memoirs, letters, interviews, novels, songs, and works of art---as well as overview information that places each document in context.
Advisors and contributors -- Acknowledgements -- About the set -- Introduction -- About the entry -- Using primary sources -- Chronology -- Beyond femininity and masculinity: perspectives on gender and sexuality -- Women's rights movement -- Gay rights movement -- Transgendereds and transsexuals -- Gender and sexuality issues in medicine and public health -- Gender and sexuality in school and the workplace -- Sex, gender, and sexuality in the media -- Obscenity, pornography, and sex crimes -- Sources consulted -- Index.
Electronic reproduction.
Keywords: Sex -- Social aspects -- History -- Sources; Sex role -- History -- Sources; Sexual orientation -- History -- Sources; Gender identity -- History -- Sources; Sex customs -- History -- Sources; Electronic books